Pengembangan Melalui Merek Produk dan Penggunaan Media Digital UMKM Berkah Bunda - Ajie Pandu Suarga; Lia Nirawati (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Indonesia is a rich, unique, and diverse country. Each region certainly its has own uniqueness or characteristics. One of characteristic in each region in general is in processed foods and drinks, can be in the form of heavy food such as pecel or snack suck as banana chips. Home-scale food of beverage sellers are usually called MSME. MSMEs are built by a person or a group, but with a small production scale or only for the business location area. Every MSMEs must have its own obtacles, ranging form raw materials, equipment, to marketing. One of the MSMEs accompanied by Group 10 KKNT-MBKM located in Jombang Regency, more precisely in Ngrimbi Village, Bareng District has problems in the product packaging process and marketing factors. Therefore, the purpose of this service is to plan marketing strategies for MSME actors so that their business runs smoothly and develops, and helps solve the obstacles experienced by MSMEs. The method used is a qualitative method with the type of data collection through observation, interviews, focus group discussions, and documentation on the activities of MSME actors. The result of the dedication that has been carried out is that the obstacles experienced by MSMEs in the product packaging process have been resolved and the marketing aspect is running well.